On the measure of the similarity between discrete (digital) images - Gary Duch, N.; Bribiesca, E. (Revista Mexicana de Ingenieria Biomedica, 2018)
The monochromatic discrete images (IDM) participate increasingly in the science and technique of our days. The images on a black and white television screen, the images that come from the satellites of prospection of earth resources are examples of this type of images.